Manajemen Program Pelatihan Kewirausahaan: Pemuda di Dinas Pemuda dan Olahraga Provinsi Sumatera Selatan - Hidayat, Rahmat; Zubaidah, Siti; Firdaus, Firdaus; Desiwantara, Desiwantara (Jurnal Publisitas, 2026)
This research is motivated by the high unemployment rate among youth in South Sumatra Province, which requires concrete efforts through empowerment and entrepreneurial capacity development. The purpose of this study is to analyze the management of the Youth Entrepreneurship Training program at the South Sumatra Provincial Youth and Sports Agency (DISPORA) to determine its effectiveness in creating independent entrepreneurs. The research method used was a qualitative case study technique, involving in-depth interviews and analysis of activity report documents. The analysis, using George R. Terry's management functions, indicated that the program's organization was well-functioning, with a clear division of committee tasks. However, in terms of planning and implementation, suboptimal outcomes were identified, particularly in the training duration, which was only effective for two of the four days due to budget constraints. This resulted in obstacles in achieving the target output of truly competent and independent participants. The conclusion of this study indicates that optimizing the entrepreneurship training program requires in-depth research into the potential interests of youth and adjustments to the implementation timeframe to ensure a more comprehensive and sustainable transfer of knowledge.